(untitled) (Palimpsesto, 2021)
This article addresses the political-cultural journals linked to the Technical University of the State of Chile (UTE) between 1947 and 1973, paying attention to the actors who constituted proposals for transformation with which they disputed the meaning frameworks around the relationship between the reform of technical education and national industrialization. Thus we identify subjects and groups that throughout their trajectory formed and reformulated intellectual, political and cultural projects that circulated through magazines, facilitating the debate based on the constitution of networks of sociability related to technical education and national industry.